Theoretical studies on di- and tetra-nuclear Ni pivalate complexes. - Rajaraman, G; Christensen, K; Larsen, F; Timco, G; Winpenny, R (2005)
A combination of DFT calculations and magnetic studies allow structural features of di- and tetra-nuclear nickel pivalate cage complexes to be deduced.